Features of teaching Russian sign language to employees of internal affairs bodies in the process of professional training - E. V. Vasilenko (Вестник Северо-Кавказского федерального университета)
Introduction. The article is devoted to the speciﬁcs of teaching employees of the internal aﬀairs bodies the basics of the Russian sign language in the process of their professional training for oﬃcial activities. People with hearing impairment or complete lack of it face various social restrictions, communication diﬃculties in everyday life.Goal. To consider the features of teaching Russian sign language to employees of internal aﬀairs bodies in the process of professional training.Materials and methods. The research is based on the generalization of the experience of teaching Russian sign language.Results and discussion. Sign language is considered a foreign language for police oﬃcers, as it has its own vocabulary, grammar and rules of sentence construction. During the analysis, optimal methods and techniques were identiﬁed that increase the eﬀectiveness of mastering educational material.Conclusion. According to the results of the study, it was concluded that in the classroom, employees master basic knowledge and skills of Russian sign language in situations of professional communication, allowing them to quickly and timely provide assistance to a deaf citizen, transmit and receive the necessary information.